Regulation effect of physical exercise on psychological stress of college students - Zhang, Yaqun (Педагогический профессионализм в образовании, физическом воспитании и спорте : материалы международной научно-практической конференции (24 апреля 2020 г.))
This study uses literature and comprehensive induction research methods to analyze the psychological stress of college students in depth, and preliminary discusses the role of physical exercise in regulating the psychological stress of college students.